2007
DOI: 10.1002/bjs.5676
|View full text |Cite
|
Sign up to set email alerts
|

Faecal incontinence

Abstract: Current treatment of faecal incontinence is evolving from a sphincter-focused view to a more holistic one, recognizing the influence of the pelvic floor and psyche in maintaining continence. Modern imaging modalities direct treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 62 publications
3
52
0
1
Order By: Relevance
“…Many techniques to treat urinary incontinence have been adapted and applied to faecal incontinence: artificial sphincters, neuromodulation of the sacral nerves, and bulking agents. [19][20][21] The adaptation of these techniques require a detailed knowledge of the topographical relations between EAS, IAS and LAM. Our study confirms the intersphincteric location of the LAM, interposed between IAS and EAS, with mean thicknesses of 1.63 mm (LAM), 2.69 mm (IAS), and 2.95 mm (EAS).…”
Section: Discussionmentioning
confidence: 99%
“…Many techniques to treat urinary incontinence have been adapted and applied to faecal incontinence: artificial sphincters, neuromodulation of the sacral nerves, and bulking agents. [19][20][21] The adaptation of these techniques require a detailed knowledge of the topographical relations between EAS, IAS and LAM. Our study confirms the intersphincteric location of the LAM, interposed between IAS and EAS, with mean thicknesses of 1.63 mm (LAM), 2.69 mm (IAS), and 2.95 mm (EAS).…”
Section: Discussionmentioning
confidence: 99%
“…Anal sphincter incompetence as well as UI can be related to pelvic floor dysfunction (25), and both should be treated concomitantly by surgical or non-surgical treatment, improving the patients' quality of life.…”
Section: Commentsmentioning
confidence: 99%
“…There is a range of treatment options for such patients. A recent systematic review of faecal incontinence reported a trend favouring conservative management, using dietary modification, biofeedback and minimally invasive procedures, including sacral neuromodulation, the SECCA  Procedure (Curon Medical, Freemont, California, USA) and the use of injectable bulking agents 2 .…”
Section: Introductionmentioning
confidence: 99%